AI IN ENGLISH EDUCATION: PURPOSES, BENEFITS AND CHALLENGES FOR 4TH SEMESTER STUDENTS AT THE UNIVERSITY OF PRIMA INDONESIA IN THE ACADEMIC YEAR 2024/2025 - Helena Yusen; Nasution, Jamaluddin; Mastaria Manurung; Cindy Maydini Sitorus; Patricia Denisu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the purposes, benefits and challenges of AI implementation faced by the fourth semester students majoring in English Department during the 2024/2025 academic year. To collect data for this study, the writers employed a qualitative research design, and the data were collected through an online platform survey namely SurveyMonkey to explore the experiences and perceptions deeply regarding AI-based learning tools. The survey revealed that most students have a preference for ChatGPT from the three other AIs that the survey had provided. Blackbox AI being second and Perplexity holding the last place. It also revealed that, even though AI is only minimally used, it’s main purpose for usage is to complete assignments, and most students find it positively helpful, with no participants picking the negative options regarding how useful AI is. Many students agree that multiple skills of theirs have improved, with developing ideas and answering questions seeing the most development. Because of this, many survey participants strongly agreed to using AI routinely, with only less than half saying a partial agreement. Despite its usefulness though, some challenges like internet issues and doubtful results still plague many answers given by AI, and misinformation still being prominent. The final conclusion this paper reached was the fact that AI has now become a prominent tool in many students academic journey and has gained incredible support as AI itself gets more and more improvements from its developers.